The Effect of Logotherapy on Grieving Stage in End Stage Renal Disease Clients - Arslan Kamil Aries; Tri Johan Agus Yuswanto; Ta'adi taadi (Jurnal Kesehatan dr. Soebandi, 2024)
Kidney failure is a disease caused by progressive damage to kidney function and generally cannot be recovered. Chronic kidney failure not only causes physiological disturbances to the client but can also cause psychological disorders, such as grieving. Providing psychological implementation can help clients to get through this period. This study aimed to determine whether there is an effect of logotherapy on the stage of grieving in clients with end stage renal disease. This study used a randomized, pretest-posttest design. The number of study sample in this study were 32 respondents who were divided into two groups, including the treatment group and the control group. The sampling technique used was simple random sampling. The results of hypothesis testing indicate that there is an effect of giving logotherapy to the stages of denial, anger, bargaining, depression, and acceptance with a p-value < 0.05, which means that there is an effect of giving logotherapy to the grieving stage of clients with end-stage renal disease. There is an effect of giving logotherapy on the stage of grieving in clients with end stage renal disease. This research is expected to be one of the references in the application of logotherapy to overcome the psychological problems of clients with end stage renal disease.